Investigation of pollutant formation of Sweet Sorghum-lignite (Orhaneli) mixtures in fluidised beds - Çubuk, MH; Heperkan, HA (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Most of the Turkish lignites have undesired fuel properties and they are extremely pollutant. In this study, Sweet Sorghum was chosen as the energy plant. Combustion experiments of lignite and lignite-Sweet Sorghum mixtures were carried out in a fluidised bed system. The fuel-feeding ratio was set such that the thermal output of the system remained constant. Addition of Sweet Sorghum to the lignite reduces the pollutant concentration. The results were supported by experimental results. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: sweet sorghum; Sorgum bicolor; lignite; co-combustion; fluidised bed; pollutant; EMISSIONS; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels